Pengaruh Giro Wadiah, Deposito Mudharabah, dan Tabungan Mudharabah Terhadap Profitabilitas Bank Syariah - Noor, Mohammad Naylu Alifi; Maslichah, Maslichah; Mawardi, M. Cholid (Universitas Islam Malang, 2023)
This study was conducted to determine the effect of wadiah demand deposits, mudharabah deposits, and mudharabah savings on the profitability of Islamic banks. This research is quantitative research. The sample of this study is the quarterly financial statements for the period March 2018-December 2022 at Islamic banks listed on the Indonesia Stock Exchange. Data analysis using multiple linear regression analysis. Based on the results of data analysis, the t-test results show that: (1) Wadiah demand deposits have no significant effect on profitability. (2) Mudharabah deposits have no significant effect on profitability. (3) Mudharabah savings have no positive effect on profitability.Keywords: Wadiah current account, mudharabah time deposit, mudharabah savings, portability.